METHODOLOGICAL ASPECTS OF MANAGEMENT OF OFFICERS OF BODIES OF STATE BORDER PROTECTION - Dziuba, P. М. (Honor and Law, 2019)
The analysis of approaches to management of operational activities and managerial activities of officers of bodies of state border protection, stated direction of the management of operational activities, a comparative analysis of the definitions and contents of the main categories for the management of operational activities, proposed a unified approach to the definition of the main categories related to the management authority of the border agencies.